Development of a knowledge-based tool for waste management of prefabricated steel structure projects - Mirshekarlou, Babak Rahmani; Budayan, Cenk; Dikmen, Irem; Birgonul, M. Talat (ELSEVIER SCI LTD, 2021)
Although the construction industry is critical for sustainability goals due to the high amount of waste it generates, its waste management performance is still not at the desired level. One of the main reasons for this can be attributed to the lack of enough knowledge of construction companies on the sources/reasons of waste and amount of waste. The major aim of this study was to develop a knowledge-based tool for capturing, storing, and disseminating waste-related knowledge for prefabricated steel construction projects. The developed tool can be used for waste estimation, monitoring, and minimization of all materials used during different phases of prefabricated steel structure projects based on the data captured from current and previous projects. One advantage of the tool is the integration of all processes of waste management, which have been usually considered independently in previous studies. Moreover, being a knowledge-based tool, it can increase awareness and learning ability of companies about waste and its management. Finally, although the process model of the tool is generic and can operate in alternative domains, the tool is applicable for only prefabricated steel projects. It is believed that the process model and the tool presented in this paper can be further customized for different project types and considering different company needs.
Keywords: Knowledge-based waste management tool; Prefabricated steel structure projects; Construction industry; Material waste; Web-based tool; CONSTRUCTION WASTE; DEMOLITION WASTE; MAIN CAUSES; INDUSTRY; SYSTEM; QUANTIFICATION; SUSTAINABILITY; MINIMIZATION; GENERATION; BUILDINGS; Science & Technology - Other Topics; Engineering; Environmental Sciences & Ecology